THE ERROR ANALYSIS OF INTERLINGUAL AND INTRALINGUAL INTERFERENCES OF THE STUDENTS: A CASE STUDY OF TOURISM STUDY PROGRAM - Sari, Putu Pande Novita; Budasi, I Gede; Adnyani, Ni Luh Putu Sri; Suwastini, Ni Komang Arie (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: This study aimed to analyze the students’ interlingual and intralingual interferences of Tourism Study Program at a State University in North Bali. A qualitative approach was applied by examining the students’ final projects of English writing for the academic year 2020/2021. In this case study, 15 final projects were chosen using the purposive sampling technique. Data collection was done through reading, note-taking, classifying, and describing. The findings revealed that the most frequent interlingual form produced by the students was using Indonesian Syntax Pattern, while the intralingual form was the simplifications. Therefore, interlingual and intralingual interferences were found in the students’ final project. There are two implications of this study, i.e. (i) teachers need to enhance their pedagogy for the teaching and learning sessions, particularly English grammar, (ii) students should learn more the English grammatical rules, which they can access many sources to learn English through watching a movie, listening to songs, talking with native speakers, reading novels and magazines. Abstrak: Penelitian ini bertujuan untuk menganalisis interlingual dan intralingual mahasiswa Program Studi Pariwisata di salah satu Universitas Negeri di Bali Utara. Pendekatan kualitatif digunakan dalam penelitian ini dengan menguji tugas akhir siswa dalam penulisan bahasa Inggris pada tahun ajaran 2020/2021. Dalam studi kasus ini, dipilih 15 tugas akhir dengan teknik purposive sampling. Pengumpulan data dilakukan melalui membaca, mencatat, mengklasifikasi, dan mendeskripsikan. Hasil temuan mengungkapkan bentuk interlingual yang paling sering dihasilkan oleh siswa adalah menggunakan Pola Sintaks Bahasa Indonesia sedangkan bentuk intralingualnya adalah penyederhanaan. Dengan dimikian, terdapat error interlingual dan intralingual dalam tugas akhir mahasiswa. Ada dua implikasi dari penelitian ini, yaitu (i) pengajar perlu meningkatkan pedagogi mereka untuk proses belajar mengajar khususnya tata bahasa Inggris, (ii) pembelajar harus mempelajari lebih lanjut aturan tata bahasa Inggris. Mereka dapat mengakses banyak sumber untuk belajar bahasa Inggris seperti menonton film, mendengarkan lagu, berbicara dengan penutur asli, membaca novel maupun majalah.